Upconverter loaded MoS2 counter electrode for broadband dye-sensitized solar cell applications - Kawya, J.; Durairaj, M.; Anandan, S.; Sabari Girisun, T. C. (Frontiers in Chemistry, 2025)
An interesting approach of including an upconverter in the MoS2 counter electrode can yield broadband light harvesting Pt-free DSSC assembly. Here different upconverter (UC) nanoparticles (Yb, Er incorporated NaYF4, YF3, CeO2 & Y2O3) were synthesized and loaded in MoS2 thin film by hydrothermal method. The inclusion of UCs in MoS2 films exposed without any secondary formation of upconverters and the uniform deposition of the films are confirmed through XRD and FESEM analysis respectively. The absorption spectrum (UV-Vis-NIR) confirms the increase in absorption intensity in visible and NIR regions due to the incorporation of UCs. Under 980 nm excitation, the UCs-loaded MoS2 films show emission in blue (450–490 nm), green (520–540 nm) and red (600–700 nm) regions due to the f-f inner transition occurring in the Er ions. The oxide and fluoride UCs-based DSSCs were fabricated with an FTO/TiO2/N719/Triiodide electrolyte/UC@MoS2/FTO assembly. Oxide UCs show greater electrocatalytic activity, which might be owed to the films exposed with more catalytic active sites favourable for ion transportation in the I−/I−3 electrolyte. Among them, higher photoconversion efficiency (PCE) of 7.1% was witnessed for (Y2O3: Er, Yb) @MoS2 counter electrode-based DSSC which is due to the good conductivity (RS) of the film, the longer electron lifetime and photon harvesting enhancement by upconversion process. It is notably convinced that the UC-loaded MoS2 films can be used as an effective counter electrode for the possible realization of upconverter DSSC and used for broadband light absorption.